A modified Agrobacterium-mediated transformation for two oomycete pathogens. - Luyao Wang; Fei Zhao; Haohao Liu; Han Chen; Fan Zhang; Suhua Li; Tongjun Sun; Vladimir Nekrasov; Sanwen Huang; Suomeng Dong (PLoS Pathogens, 2023)
Oomycetes are a group of filamentous microorganisms that include some of the biggest threats to food security and natural ecosystems. However, much of the molecular basis of the pathogenesis and the development in these organisms remains to be learned, largely due to shortage of efficient genetic manipulation methods. In this study, we developed modified transformation methods for two important oomycete species, Phytophthora infestans and Plasmopara viticola, that bring destructive damage in agricultural production. As part of the study, we established an improved Agrobacterium-mediated transformation (AMT) method by prokaryotic expression in Agrobacterium tumefaciens of AtVIP1 (VirE2-interacting protein 1), an Arabidopsis bZIP gene required for AMT but absent in oomycetes genomes. Using the new method, we achieved an increment in transformation efficiency in two P. infestans strains. We further obtained a positive GFP transformant of P. viticola using the modified AMT method. By combining this method with the CRISPR/Cas12a genome editing system, we successfully performed targeted mutagenesis and generated loss-of-function mutations in two P. infestans genes. We edited a MADS-box transcription factor-encoding gene and found that a homozygous mutation in MADS-box results in poor sporulation and significantly reduced virulence. Meanwhile, a single-copy avirulence effector-encoding gene Avr8 in P. infestans was targeted and the edited transformants were virulent on potato carrying the cognate resistance gene R8, suggesting that loss of Avr8 led to successful evasion of the host immune response by the pathogen. In summary, this study reports on a modified genetic transformation and genome editing system, providing a potential tool for accelerating molecular genetic studies not only in oomycetes, but also other microorganisms.